Firm growth in multinational corporate groups - Harald Oberhofer; Michael Pfaffermayr (University of Innsbruck, Department of Public Finance, 2008)
This paper formulates an econometric firm growth model that explicitly accounts for the interdependence of firm performance within corporate networks and is in line with several economic theories on firm growth. We estimate the model for national and multinational corporate groups (MNEs) using a recently introduced instrumental variable estimation procedure for peer group effects developed by Lee (2007). In our data for corporate groups the observation of fast growing young firms and slow growing old firms disappears if interdependence of firm performance within corporation networks is introduced.
Keywords: C21; F23; L25; 330; firm growth; size adjustment; corporate groups; multinational activity; peer-group effect estimation; Unternehmenswachstum; Betriebsgröße; Unternehmenskooperation; Multinationales Unternehmen; Europa